DETERMINANTS OF THE PERFORMANCE OF THE POLITICAL SYSTEM IN NIGERIA (A STUDY IN POLITICAL GEOGRAPHY) (World Bulletin of Social Sciences, 2023)
The performance of the political system in Nigeria is controlled by several overlapping and intertwined determinants, including the regional factor represented by the division of the state into states and local councils of government, which did not affect the ethnic division of the state on the basis of tribes. In northern Nigeria and their orientation towards declaring their independent state, which adds a state of confusion to the political reality in light of the emerging tensions as well as the lack of security due to the presence of armed conflicts in the neighboring countries of Nigeria such as Chad and Niger and the tribal entanglement with the inhabitants of those countries whose impact was reflected on the Nigerian interior such as political assassinations and ethnic conflicts Maritime piracy, oil smuggling, currency counterfeiting, and political conflicts between political parties and forces had a negative impact on the democratic application of the transparency and integrity of the elections.